Digital Convergence Of Islamic Boarding School: Bridging Tradition And Modernity In Public Engagement - Rizkiyah Hasanah; Ahmad Nadif Sanafiri; Zohaib Hassan Sain (Visionaria: Journal of Educational Innovation Management, 2025)
The digital transformation in education has brought significant changes to communication, learning, and public engagement patterns, including in Islamic boarding schools (pesantren). As traditional Islamic educational institutions, pesantren face the challenge of maintaining classical values while responding to modern demands through digital convergence. This study aims to explore how pesantren utilize digital technology as a bridge between Islamic tradition and the demands of modern society, fostering broader public engagement. The research method used is a qualitative approach with case studies of several pesantren that have integrated digital media into education, da'wah, and institutional management. Data were obtained through interviews, observations, and documentation analysis. The results show that digital convergence not only expands access to information and pesantren communication networks but also strengthens their public image through social media, websites, and online learning platforms. However, challenges arise related to human resource readiness, digital literacy, and the risk of degradation of traditional values. This study's contribution lies in presenting a model for integrating pesantren traditions with relevant digital technology to strengthen the role of Islamic education in responding to the needs of the modern era, while also affirming the pesantren's identity as centers of knowledge, morality, and social engagement.